Appropriation cinema at the dawn of the digital age: reflections from Harun Farocki’s work - Flores Fernández, Camila (2020)
Harun Farocki's work (1944-2014) has spanned for more than five decades, and has dealt primarily with the image, its meanings, its relationship with the mass ideology, and the possibilities and limits of its automation and mechanization in the digital age. Through the found footage technique, Farocki has established throughout his career different analytical strategies that have allowed him, through his film works, to propose an exhaustive review and criticism of the image and its implications. This essay seeks to propose reflections, based on Farocki's work, about the politics of the image, the relationship with the author / producer and its role in ideological, political and social spheres.